Determinants of Competitive Negotiation Style in Agribusiness Trade of High Value Food Crop Products in Tanzania: Evidence from Middlemen in Arusha, Tanzania - Chonjo, Harrison; Ngaruko, Deus D.; Lyanga, Timothy (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This paper explored the role of competitive negotiation style in agribusiness food value addition in Tanzania with insights from Arusha, Tanzania. Cross sectional survey of 280 middlemen were involved in the commodity’s value chain in Arusha main markets. A multiple regression analysis was conducted to determine main factors contributing to competitive negotiation style but also on their disaggregated effect on agribusiness trade performance. The results showed that competitive negotiation style through self view point, self gain, self win and self outcome had a negative effect on agribusiness performance. In this study it was found that competitive negotiation style had negative significant impact on agribusiness trade performance. The model had high concern for self and low concern for others. The low concern for others had been founded to add negative performance and made it to be the highest negative impacted model. In this notion once one side of the negotiating part found to have less considered by other part the negotiation process tends to be hard with negative performance. It was concluded that competitive negotiation style was not effective model on high value crops but it can be done in a non-competing way (competing-un-competing). Competitive negotiation style can further be reflected on diplomatic arena as non-productive way of conflict and disputes management, in leadership and interpersonal relationship.